Transient Hydroureteronephrosis Caused by a Foley's Catheter Tip in the Right Ureter - Jacob George; George Tharion (The Scientific World Journal)
We report a case of unilateral hydronephrosis following urethral catheterization in a patient with T6 complete paraplegia at the Physical Medicine and Rehabilitation Department in a tertiary care teaching hospital, India. Diagnosis was established by an abdominal ultrasound. The misplaced catheter tip was withdrawn from the ureteric orifice and hydronephrosis was resolved. Foley's catheterization, a widely practiced clinical procedure, is not without its attendant risks of an inadvertent placement in the ureter leading to transient hydronephrosis. Inadequate drainage through a catheter should thus alert one to this potentially hazardous complication that can be diagnosed by an early ultrasound. This complication can be avoided by gently tugging on the catheter after inflating the catheter bulb.